1988
DOI: 10.1073/pnas.85.14.5072
|View full text |Cite
|
Sign up to set email alerts
|

Channel-forming properties of cecropins and related model compounds incorporated into planar lipid membranes.

Abstract: Cecropins, positively charged antibacterial peptides found in the cecropia moth, and synthetic peptide analogs form large time-variant and voltage-dependent ion channels in planar lipid membranes in the physiological range of concentration. Single-channel conductances of up to 2.5 nS (in 0.1 M NaCl) were observed, which suggests a channel diameter of 4 nm. Channels formed by the peptides cecropin AD and MP3 had a permeability ratio of Cl-/Na+ = 2:1 in 0.1 M NaCI. A comparative study of the three cecropins, cec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
353
0
6

Year Published

1992
1992
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 486 publications
(374 citation statements)
references
References 32 publications
15
353
0
6
Order By: Relevance
“…This suggests that the complex permeabilizing the membrane consists of some five monomers. From our (Christensen et al, 1988) and melittin (Tosteson et al, 1988) have been shown to exhibit similar properties. Finally, in E. coli, magainin 2 does not release @-galactosidase from the cells it kills (J. L. Rosner and H. V. Westerhoff, unpublished).…”
Section: Discussionmentioning
confidence: 55%
“…This suggests that the complex permeabilizing the membrane consists of some five monomers. From our (Christensen et al, 1988) and melittin (Tosteson et al, 1988) have been shown to exhibit similar properties. Finally, in E. coli, magainin 2 does not release @-galactosidase from the cells it kills (J. L. Rosner and H. V. Westerhoff, unpublished).…”
Section: Discussionmentioning
confidence: 55%
“…30 A-thick membrane of a bacterial cell. Most of these peptides could be viewed as two 0t-helical segments separated by a Gly-Pro-eontaining 'hinge' region providing the necessary conformational flexibility required for membrane channel formation [15,19,20]. In the previously described CA(1-13)M(I-13) and CA(I-S)M(1-18) hybrids, the melittin-derived Gly-Ile-GiyAla tetrapeptide located at the middle of the sequence might play a similar role.…”
Section: Discussionmentioning
confidence: 99%
“…Structural studies of the antimicrobial peptides have revealed two main structural motifs. One, the a-helical motif, functions as an ion channel to perturb the membrane of the microorganism [7]. Mellitins and cecropins are included in this class.…”
Section: Introductionmentioning
confidence: 99%